Comparative Characteristics of Biomaterials from Juvenile Dentin and Brefomatrix Using Raman Spectroscopy - Elena V. Timchenko; Irina V. Bazhutova; Pavel Е. Timchenko; Oleg О. Frolov; Larisa Т. Volova (Biophysica, 2022)
The results of studies on the assessment of new biomaterials from juvenile teeth for further use in surgical dentistry for bone tissue repair are presented in this work. The comparative assessment of these materials and brefomatrices used in dentistry was carried out. It was shown that spectral properties of new biomaterials from juvenile dentin were similar to the spectral properties of brefomatrices from cortical tissue according to the developed discriminant model of the characteristic changes of Raman line intensities. The calculated accuracy of the discriminant model was 82.7 ± 3.2%.